GE_GERICHTE P/13505/2016 vom 27. Juni 2018 - GE Cour de justice (2018)
FIXATION DE LA PEINE ; PEINE COMPLÉMENTAIRE ; MOBILE ; RÉPARTITION DES FRAIS ; DÉPENS | LEtr.115.letb; CP.47; CP.52; CP.48.al1.leta; CPP.426.al1; CPP.429.al1.leta